SISTEM AKUNTANSI PENGELUARAN KAS PADA PT FEDERAL IZUMI MANUFACTURING - Hamizar; Samsul Bahri; Kuswandi (DIVERSITY: Journal of Multi Science Linearity, 2024)
In every transaction activity in the company always affects the cash balance. Because the nature of cash is very easy to embezzle and misappropriate. So it is important to have an adequate accounting system so that the realization and use of cash can really be used to cover the company's costs. The accounting system is a cash disbursement accounting system. The purpose of this study is to determine the cash disbursement accounting system in terms of the parts involved, the documents required, the accounting records used, the procedures required, and the internal control system implemented by the company. The research methodology used is a field study by means of observation, interviews and literature studies. The steps used are to discuss the implementation of the Cash Disbursement System and Procedures at PT Federal Izumi Manufacturing. The results of the study show that the cash disbursement accounting system at PT Federal Izumi Manufacturing is fairly good, from the appropriate parts and functions, procedures, records and internal control elements to the complete and fairly good, only for the cash disbursement evidence document, namely the payment slip, only one document is made so that if the document is lost, the company does not have a backup for the document